Knowledge Transfer in the Mirror: Reflections on the Determinants of Research Groups and Companies Collaborative Patterns within Andalusia's Regional Innovation System - Hugo Pinto (European Regional Science Association (ERSA), 2011)
Knowledge transfer is a crucial aspect for the new paradigm of science-industry cooperation. The new role of universities and the relevance of external knowledge to firm's competitiveness brought a huge attention to this process both in analytical and decision-making terms. Commonly, formal mechanisms as intellectual property rights licensing, research contracts and spinning-off are the focus of the policy interventions and studies but the role of informality is being underlined by several recent research results. This article explores the crucial factors that induce science and industry collaborations in Andalusia, a catching-up region in Spanish and European context. The study uses limited dependent and count data regression analysis based in a survey applied in parallel to research groups and firms. The estimated regressions create a mirror image between these two institutional spheres stressing aspects that are more relevant in each reality to stimulate the existence, number, diversity and informality of knowledge transfer. The results give relevant insights for policies to stimulate knowledge transfer in technology moderate intensive South European regions.
Keywords: 330